2016
DOI: 10.1080/02626667.2015.1125482
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid factorial stepwise-cluster analysis method for streamflow simulation – a case study in northwestern China

Abstract: In this study, a hybrid factorial stepwise-cluster analysis (HFSA) method is developed for modelling hydrological processes. The HFSA method employs a cluster tree to represent the complex nonlinear relationship between inputs (predictors) and outputs (predictands) in hydrological processes. A real case of streamflow simulation for the Kaidu River basin is applied to demonstrate the efficiency of the HFSA method. After training a total of 24 108 calibration samples, the cluster tree for daily streamflow is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…According to the five statistical coefficients, both the two schemes yielded acceptable simulation in all three stations. This result is consistent with previous studies (Fan et al, 2015;Li et al, 2015;Fan et al, 2016;Zhuang et al, 2016) which indicated that stepwise cluster analysis can provide reliable and efficient flow prediction. In the calibration period, measured and simulated monthly stream flows have a good match using the two schemes.…”
Section: Deterministic Predictionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the five statistical coefficients, both the two schemes yielded acceptable simulation in all three stations. This result is consistent with previous studies (Fan et al, 2015;Li et al, 2015;Fan et al, 2016;Zhuang et al, 2016) which indicated that stepwise cluster analysis can provide reliable and efficient flow prediction. In the calibration period, measured and simulated monthly stream flows have a good match using the two schemes.…”
Section: Deterministic Predictionsupporting
confidence: 93%
“…stepwise cluster analysis has received much attention for environmental issues such as air quality prediction (Huang, 1992), process control (Huang et al, 2006), climate projections (Wang et al, 2013), stream flow prediction (Cheng et al, 2016;Zhuang et al, 2016), groundwater simulation (Han et al, 2016), and ecosystem analysis and prediction (Sun et al, 2018). This previous researcher has indicated that the stepwise cluster analysis approach can characterize environmental processes with complicated nonlinear and dynamic relationships and provide satisfactory predictions.…”
Section: Framework Of Stepwise Cluster Analysis Hydrological Modelmentioning
confidence: 99%
“…The framework of the developed approach is presented in Figure 1. SCA was introduced by Huang (1992) and has been widely used in pieces of environmental research, such as climate change, air pollution, process control, and hydrology prediction (Huang et al, 2006;Wang X. Q. et al, 2013;Li et al, 2015;Wang and Huang, 2015;Fan et al, 2016;Zhuang et al, 2016;Sun et al, 2019;Zhai et al, 2019;Duan et al, 2020;Ren et al, 2021b;Wang et al, 2021). These studies have indicated the SCA has satisfactory performance in projecting environmental processes with complex non-linear and dynamic relationships.…”
Section: Stepwise-clustered Simulation Approach For Projecting Future Heat Wavesmentioning
confidence: 99%
“…Previously, statistical downscaling methods mostly assume that the interested dependent variable is a function of independent variables (Wilby et al, 2002;Hessami et al, 2008;Gibson et al, 2017), while the improvements of the quality of downscaled simulation reproduced through such a function are likely to be limited relative to the raw GCMs' output owning to the complex climate system (Wilby et al, 2002;Wang X. Q. et al, 2013). However, the underlying complex relationships (including non-linear and discrete relationships) between dependent and independent variables can be revealed by the generated cluster tree without assuming the functional relationship compared to these downscaling methods (Wang X. Q. et al, 2013;Zhuang et al, 2016;Duan et al, 2020). Handling the complicated relationship among multiple dependent and independent variables at the same time is another significant advantage of SCA (Fan et al, 2015;Wang et al, 2021).…”
Section: Stepwise-clustered Simulation Approach For Projecting Future Heat Wavesmentioning
confidence: 99%
“…Nevertheless, besides its calculation complexity, the performance of the SCA is sensitive to its inputs and internal parameters; the difference within leaf clusters of a SCA tree is usually not well described. The SCA has been applied to various water resources and environmental management problems, such as urban air quality prediction (Huang, 1992), lung cancer diagnosis (Ren et al, 1997), waste treatment process simulation (Sun et al, 2009;Sun et al, 2011), groundwater bioremediation optimization (Huang et al, 2006;Qin et al, 2007;He et al, 2008b;Wang et al, 2012;Zhao et al, 2017), open water forecasting (Fan et al, 2015;Li et al, 2015;Han et al, 2016;Zhuang et al, 2016b;Cheng et al, 2016;Fan et al, 2017;) and climate model downscaling (Wang et al, 2013;Zhuang et al, 2016a;Zhai et al, 2019). However, few applications of SCA to river ice forecasting are reported.…”
Section: Introductionmentioning
confidence: 99%